CARACTERIZAÇÃO DAS ALTERAÇÕES AMBIENTAIS SEGUNDO O USO DOS RECURSOS NATURAIS POR TRABALHADORES RURAIS NO ALTO CURSO DO RIO PERICUMÃ. - Pereira, Regina Célia de Castro (2006)
The characterization of the environment changes from the development of activities is approached in this study caused by human activities in their different ways of interaction society-nature, in the area of the high course of river Pericumã, one of the main basins of the area called Baixada Maranhense. It was considered that the population that use natural resources through traditional techniques have ample knowledge of the daily natural phenomena, registering the occured changes therefore keeps a straight relation with the environment. This study is based on the theorical foundations of human ecology and etnobiology, that analize interactive processes of human being through the use of natural resources and the valuation of the traditional knowledge, giving to approach agricultural activity, fishing, and activities with animals. It was proceeded with open questionnaires with the inhabitants and community representatives. It was considered for the sample resident people had at least ten years in the located towns next the river that drain the high course of the river Pericumã, the choice of the area was justified by the little scientific production in this basin, that has a great importance for the population resident in the cities drained for it.. It was proceeded analysis from the data using a software of statistical treatment and geoprocessing that had provided to the characterization of the perceived changes and identification of their causes. The data of the perception of the inhabitants indicate straight relation between the environment alterations and the population increment, aggravated for the social and economic conditions of the population. The period of training of the ambient impacts still does not characterize, the ambient degradation.